Examining Teaching Materials in Higher Education Against Religious Intolerance and Pluralism in the Global Era: Islamic Perspective - Sitti Jamilah (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
This study aims to investigate the role of the study of teaching materials in universities on religious intolerance and pluralism. The study also explores the Islamic perspective on these two dimensions. The location of the research was carried out at the IAIN Parepare of South Sulawesi Province, Indonesia. The source of research data is secondary data obtained from document review of teaching materials in the Aqidah Akhlak (moral theology) course as well as literature relevant to the research topic. The literature study research methodology guided by content analysis focuses on three topics, namely teaching materials, religious intolerance, and pluralism in the view of Islam. The study revealed two findings. First, the results of a study of the components or the appropriateness of the contents of the items of teaching materials in accordance with the values ​​of tolerance as contained in Pancasila and Bhineka Tunggal Ika. Thus, these teaching materials contribute to preventing religious intolerance and provide a new perspective on pluralism. Second, in the view of Islam, it is known that religious intolerance can be avoided by tasamuh, namely by instilling a commendable moral attitude. While pluralism there are two opposing schools between those who accept and reject. In the Qur'an, there is an explanation of pluralism as a necessity, human diversity in togetherness. The conclusion is that the study of teaching materials contributes to supporting tasamuh behavior and avoiding negative views about pluralism. Pluralism is not recommended, namely religious pluralism which is feared to have a negative impact on aqidah. With the study of teaching materials, negative possibilities can be minimized as long as they are in accordance with practice. Because after all, the values ​​of pluralism are also able to foster mutual respect and appreciation between fellow human beings so that they can support the development of student morality. The expected implication is that universities must supervise and provide input on teaching materials that have the potential for the concepts of tolerance and pluralism. The government needs to support the socialization of the true importance of tolerance and pluralism in the campus environment.